2020
DOI: 10.1049/iet-rpg.2019.0804
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of system efficiency and utilisation factor of a mirror integrated solar PV system

Abstract: This study presents the investigation of benefits obtained in a mirror integrated standalone photovoltaic (PV) test system of 0.3 kW capacity. The enhancement of energy extraction is possible only through fixing the mirror at an optimal angle facing towards the PV panel. Hence, the optimal condition for the maximum energy extraction in a year at a specific location is derived and presented considering the total irradiation falling on the panel. A detailed estimation on performance indices and feasibility analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Another experimental investigation was recently carried out in India on a mirror integrated PV system (MIPVS). It is concluded that the MIPVS system produces a 30.3% enhancement in yearly energy output compared to the conventional PV system (Odungat et al 2020). Amanlou et al investigated theoretically using CFD, an air-cooled LCPV/T system with a new design concave-side walls diffuser.…”
Section: Concentrating Photovoltaic Thermal Cpv/t Systemsmentioning
confidence: 99%
“…Another experimental investigation was recently carried out in India on a mirror integrated PV system (MIPVS). It is concluded that the MIPVS system produces a 30.3% enhancement in yearly energy output compared to the conventional PV system (Odungat et al 2020). Amanlou et al investigated theoretically using CFD, an air-cooled LCPV/T system with a new design concave-side walls diffuser.…”
Section: Concentrating Photovoltaic Thermal Cpv/t Systemsmentioning
confidence: 99%